APPLYING CLIL METHOD FOR A COMPREHENSIBLE INPUT IN READING SKILL - Dahik Solis, Cecilia Elizabeth; Càneppa Muñoz, Cecilia Isabel; García León, Erika Paola (Revista Pertinencia Académica. ISSN 2588-1019, 2017)
APLICACIÓN DEL MÉTODO CLIL EN LA DESTREZA DE LECTURA COMPRENSIVA ABSTRACT The lack of students’ interest in upgrading Reading skill in a low percentage is perhaps, due to the fact that people are not accustomed to read in their spare time in many countries, even for their schooling duties. For many years, the development of reading activities in class has normally been carried out in a simple way, with simple instructions which have not let the learners be in depth with their contents. It means that it has been performed superficially without providing comprehensible input to the students. This research focus on how well CLIL methodology maximizes reading comprehension and the acquisition of the new language in contrast with the methodology applies in the Direct Method. (Rosenshine, 1985 as cited in Silver, Strong, Perini, 2007) says that “Teachers who spend more time demonstrating and explaining procedures and skills are more effective than teachers who spend less time doing so.” The findings of this study show that reading skills developed with the CLIL methodology would be helpful to enhance students’ communicative skills and motivation taking into account the time devoted to performing tasks in class, the aim of each activity, the knowledge that the students get and the outcomes that the students could get at the end of the English teaching and learning process. KEYWORDS: reading comprehensible input, activities, outcomes, CLIL and Direct methods, communicative skills. RESUMEN El poco interés de los estudiantes en desarrollar la destreza de comprensión lectora es debido talvez a que las personas no han adquirido el hábito de la lectura en su tiempo libre ni tampoco en sus obligaciones escolares. Por muchos años la aplicación de actividades dentro de la lectura ha sido realizada de manera simple con instrucciones simples que no han permitido que los estudiantes tengan una real comprensión del texto que leen basadas en sus opiniones y pensamiento crítico. Esta superficialidad en las actividades denota que no se provee de una comprensión significativa donde no se internaliza el contenido leído. Esta investigación se enfoca en como la metodología CLIL puede maximizar la comprensión lectora y la adquisición del idioma extranjero en contraste con la metodología del Direct method. (Rosenshine, 1985 citado en Silver, Strong, Perini, 2007) dice “Los profesores que pasan más tiempo explicando y demostrando procedimientos y destrezas son más efectivos que los que no lo hacen.” Los resultados de este estudio demuestran que la destreza de la lectura desarrollada con la metodología CLIL sería útil para mejorar las destrezas comunicativas y motivación en los estudiantes tomando en consideración el tiempo empleado en clase para realizar las actividades, los objetivos de cada actividad, el contenido transmitido a los estudiantes y los resultados que los estudiantes podrían conseguir al final del proceso de enseñanza-aprendizaje del idioma inglés. PALABRAS CLAVE: Lectura comprensiva; actividades; resultados; métodos CLIL and Direct; destrezas comunicativas.